Mediators Linking Childhood Adversities and Trauma to Suicidality in Individuals at Risk for Psychosis - Schmidt, Stefanie J.; Schultze-Lutter, Frauke; Bendall, Sarah; Groth, Nicola; Michel, Chantal; Inderbitzin, Nadja; Schimmelmann, Benno G.; Hubl, Daniela; Nelson, Barnaby (Frontiers in Psychiatry, 2017)
Suicidality is highly prevalent in patients at clinical high risk (CHR) for psychosis. Childhood adversities and trauma are generally predictive of suicidality. However, the differential effects of adversity/trauma-domains and CHR-criteria, i.e. ultra-high risk and basic symptom criteria, on suicidality remain unclear. Furthermore, the underlying mechanisms and thus worthwhile targets for suicide-prevention are still poorly understood. Therefore, structural equation modeling was used to test theory-driven models in 73 CHR-patients. Mediators were psychological variables, i.e. beliefs about one’s own competencies as well as the controllability of events and coping styles. Additionally, symptomatic variables (depressiveness, basic symptoms, attenuated psychotic symptoms) were hypothesized to mediate the effect of psychological mediators on suicidality as the final outcome variable. Results showed two independent pathways. In the first pathway, emotional and sexual but not physical adversity/trauma was associated with suicidality, which was mediated by dysfunctional competence/control beliefs, a lack of positive coping strategies and depressiveness. In the second pathway, cognitive basic symptoms but not attenuated psychotic symptoms mediated the relationship between trauma/adversity and suicidality. CHR-patients are thus particularly prone to suicidality if adversity/trauma is followed by the development of depressiveness. Regarding the second pathway, this is the first study showing that adversity/trauma led to suicidality through an increased risk for psychosis as indicated by cognitive basic symptoms. As insight is generally associated with suicidality, this may explain why self-experienced basic symptoms increase the risk for it. Consequently, these mediators should be monitored regularly and targeted by integrated interventions as early as possible to enhance resilience against suicidality.